Hybrid solar power system versus photovoltaic plant: A comparative analysis through a life cycle approach. (January 2019) - Magrassi, Fabio; Rocco, Elena; Barberis, Stefano; Gallo, Michela; Del Borghi, Adriana
Abstract: The sun is considered to be one of the most environmentally sound sources of clean and renewable energy. Nevertheless, new hybrid solar plants - combining solar power with another source of energy - have never been compared to traditional solar technologies. Therefore, the aim of this work is to compare the potential environmental impact of a 100 kWp photovoltaic plant (PV) with a 100 kW hybrid solar-gas turbine system (SHGT) using a life cycle assessment methodology. To the best of our knowledge, this type of comparison is the first of its kind. The analysis is performed considering three different scenarios for the SHGT. Additionally, a deep sensitivity analysis is undertaken, focusing on those parameters that mostly influence the outcomes. The results highlight that, using the currently available technology, PV resulted to be the best environmental choice, with greenhouse gas (GHG) emission of 0.043 kg CO2eq /kWh. SHGT plant emissions resulted to be higher, equal to 0.236 kg CO2eq /kWh when running at nominal power 12 h/day, mainly due to the fuel contribution. However, improvements in receiver technology could make it possible to reach higher receiver outlet temperatures and consequently save fuel, reducing the overall environmental impact. Moreover, replacing the natural gas used as turbine running fuel with solar radiation leads to a reduction in GHG emissions, which become comparable to PV plant gases. Highlights: PV are a better environmental solution in comparison with SHGT. The location of plants has a high influence on the final results. Sizing of the heliostat field is very important to ensure good solar performance. SHGT systems will improve their environmental scores whit technology enhancements.